Safety at The William Quarrier Scottish Epilepsy Centre. (December 2017) - Anderson, James; Grant, Victoria; Elgammal, Mariam; Campbell, Alison; Hampshire, Julia; Hansen, Stig; Russell, Aline J.C.
Abstract: Purpose: We examined the yield from EMFIT bed alarms and staff response time to generalised seizure in a medium term residential assessment unit for epilepsy. Methods: The Scottish Epilpesy Centre (SEC) has a Video Observation System (VOS) that provides continuous recording of all patient spaces (external and internal) and allows retention of clinically relevant events. A retrospective audit of daily EMFIT test records, nursing seizure record sheets (seizure type and EMFIT alert status), clinical incident reporting systems and the VOS database of retained clinical events was conducted for an 9 month period from April 1st 2016 till December 31st 2016. All generalized tonic clonic seizures (GTCS) were noted by patient, time and location and staff response time to GTCS was calculated. Results: There were 85 people admitted during the audit period who had 61 GTCS. 50 events were in bed and EMFIT alert status was recorded. On 8 occasions the EMFIT did not alert: 5 events were not of sufficient duration or frequency, in 2 the patient fell from the bed early and 1 event the alarm did not trigger. The average response time to GTCS was 23 s. The longest response time was 69 s (range, 0–69 s, sd 15.76.). Conclusions: The EMFIT bed alarm appears to be a valuable adjunct to safety systems. Within the novel environment of the SEC it is possible to maintain a response time to GTCS that is comparable to hospital based UK video telemetry units.